Nationalising local sustainability: Lessons from the British wartime Utility furniture scheme. (October 2015) - Pinch, Philip; Reimer, Suzanne
Highlights: Illustrates lessons of Utility furniture scheme for current sustainability debates. Argues for the strategic importance of 'pragmatic centralism' at times of crisis. Foregrounds role of state as organising agent in commodity networks. Abstract: Analyses of sustainable design and commodity networks often make a priori assumptions about the capacity of markets to provide solutions to environmental problems; and have a tendency to celebrate local scales of action. This paper offers a contrasting account, in which the national state sought to carefully manage scarce natural resources and to ensure equitable consumption at a time of deep crisis. We utilise the historical example of the British wartime Utility furniture scheme in order to draw out three lessons for sustainable and equitable environmental practice. First, we argue that national states do not simply provide an institutional backdrop to sustainable production but rather can act as important organising agents. Second, the paper emphasises that sustainability is best achieved through interventions across a commodity network, beyond simply modifications to a single node such as design. Finally, we underscore the value of 'pragmatic centralism' in environmental decision-making, calling attention to the collaborative practices that underpinned the scheme. The example of Utility's adaptive responses—borne out of crisis, scarcity and shortage during wartime—offers much that is of intrinsic interest to current concerns about resource consumption and the drivers of sustainability in commodity networks.